2010
DOI: 10.2147/opth.s10521
|View full text |Cite
|
Sign up to set email alerts
|

Effect of travoprost on 24-hour intraocular pressure in normal tension glaucoma

Abstract: Purpose: The effect of travoprost 0.004% on 24-hour intraocular pressure (IOP) was examined in patients with normal tension glaucoma (NTG). Subjects and methods: This study included 17 patients with newly diagnosed unilateral NTG. IOP was measured at three-hour intervals over 24 hours by Goldman applanation tonometer in patients taking topical travoprost 0.004% and was compared retrospectively with 24-hour IOP data in untreated eyes. Results: IOP values were significantly reduced at individual time points afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Nomura et al performed the only study reporting on the 24-hour effects of travoprost in NTG. 13 In their study, mean 24-hour IOP was reduced from 12.9 mmHg to 10.3 mmHg (20% reduction). Of note in their protocol, subjects were awoken and walked to a slit lamp to perform IOP readings in an upright position overnight.…”
Section: Discussionmentioning
confidence: 88%
“…Nomura et al performed the only study reporting on the 24-hour effects of travoprost in NTG. 13 In their study, mean 24-hour IOP was reduced from 12.9 mmHg to 10.3 mmHg (20% reduction). Of note in their protocol, subjects were awoken and walked to a slit lamp to perform IOP readings in an upright position overnight.…”
Section: Discussionmentioning
confidence: 88%
“…In view of the suggestion of setting a more comprehensive management target regarding patients' 24-hour IOP profiles, we have also discussed the effectiveness of glaucomatous medications, laser trabeculoplasty, and trabeculectomy in optimizing various 24-hour IOP parameters. According to current data, prostaglandin analogues (especially bimatoprost and travoprost [51, 85]) were the most effective topical eyedrops to achieve a uniform 24-hour IOP reduction [8386], and they were also effective in reducing the maximum and minimum IOP and short-term IOP fluctuations [87]. In particular, evening administration of prostaglandin analogues was shown to be better than morning dosing to lower daytime IOP in patients with POAG [19, 81, 83, 92].…”
Section: Discussionmentioning
confidence: 99%
“…Stewart et al conducted a meta-analysis of studies that assessed the 24-hour efficacy of antiglaucoma medications and concluded that bimatoprost followed by travoprost were the two most effective IOP-reducing medications [51, 85]. In patients with newly diagnosed NTG, topical travoprost (0.004%) was shown to significantly reduce mean IOP, maximum and minimum IOP, and short-term IOP fluctuations [87]. Seibold and Kahook found that travoprost significantly lowered IOP at all time points during diurnal and nocturnal periods in an interventional trial involving 27 NTG patients [88].…”
Section: Therapeutic Efficacy Of Current Glaucoma Management Modalmentioning
confidence: 99%
“…Travoprost with sofZia® use has been reported in limited numbers of NTG patients, with a potent IOP lowering effect and minimal corneal damage. 12 , 13 We, therefore, expanded on these findings and conducted a study with a large number of Japanese NTG patients.…”
Section: Discussionmentioning
confidence: 99%